Fast Facts: Lymphoma - Hatton, Chris; Collins, Graham; Sweetenham, John (S. Karger, 2018)
Lymphoma affects all ages. Advances in diagnostic cellular and molecular techniques coupled with new treatment options are improving patient outcomes.This third edition of our bestselling 'Fast Facts: Lymphoma' distills the most important aspects of diagnosis and management into an up-to-date and highly accessible well-illustrated overview that includes:• a clear outline of the nature of lymphoma• the essentials of clinical presentation, biopsy and histology• a synopsis of current laboratory diagnostics, including immunophenotyping, cytogenetics and microarray technology, and updated to include the latest molecular genetic techniques• key aspects of staging and initial therapy• clearly illustrated overviews of the pathology, presentation, treatment and prognosis of each lymphoma subtype• new treatment options, including targeted biological therapies and chimeric antigen receptor T cells (CAR T cells)• a practical overview of supportive care for the complications of lymphoma.Written by three lymphoma experts from the UK and USA, 'Fast Facts: Lymphoma' gives an interesting international perspective to this challenging disease. Its clarity and colorful format make it a valuable resource for senior health professionals seeking an accessible update in this area of hemato-oncology, trainee doctors and specialist nurses who are new to it, and individuals affected by lymphoma and seeking more information.Contents:• Epidemiology• Cellular and molecular aspects• Presentation, biopsy and diagnostic laboratory techniques• Staging and general management principles• Aggressive B-cell lymphomas• Indolent B-cell lymphomas• T-cell and natural-killer cell lymphomas• Immunocompromised and HIV-positive patients• Hodgkin lymphoma• Treatment modalities• Supportive care
Keywords: hematologie a transfuzní lékařství; Hematology; hematologie; lymfom; onkologie; Lymphoma